Psychological features of the development of sanogenic potentialas a factor in the professional sustainability of the personality of the future psychologist - Varina, H. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The scientific article is devoted to the problem of determining the characteristics of the sanogenic potential as a factor in the professional stability of the personality of a future psychologist-practitioner. The urgency of the problem is determined by the conditions for optimizing the personality-professional development of future practicing psychologists, personal maturity, the integration of self-concept and the development of a person’s sanogenic potential as aspects of professional stability, effective professional self-realization and the factors of preserving a person’s mental health.In order to develop the sanogenic personality potential of future psychologists, a training program "Development of the sanogenic personality potential: stress resistance and time management" was developed on the basis of a stress model. The purpose of the program is to increase the overall level of sanogenic potential of the individual. Particular attention is paid to forming a positive image of a stressful situation, learning to cognitively analyze the situation, predicting behavior as appropriate, updating the skills of arbitrary relaxation and developing experience in applying techniques and formulas for constructive response in solving professional problems. The program is created in accordance with the principles of the concept of accelerated learning (Accelerated Learning Theory) and uses all the latest developments in the field of adult learning methodology.Analyzing the results, we can say that the psycho-correction program has helped to increase the level of emotional stability and sanogenic potential of future psychologists. Students have decreased levels of situational and personal anxiety, decreased levels of feelings of insecurity, anxiety, inferiority, anxiety about work, sensitivity to failure (reflects the scale of "emotional"), increased the level of flexibility of thinking and behavior, ability to change shows the plasticity scale).
Keywords: professional stability; stress tolerance; sanogenic potential; emotional stability; adaptation